2018
DOI: 10.1002/aorn.12445
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hyperglycemia: A Literature Review

Abstract: The purpose of this literature review is to examine current evidence and determine the effects of stress hyperglycemia on patient outcomes during the perioperative period. This review summarizes the pathophysiology of stress hyperglycemia, the population it affects, and strategies for optimal treatment to reduce the potential for postoperative complications. A literature search produced 16 of the most current studies on the effect of stress hyperglycemia in both the diabetic and nondiabetic populations. The ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Cannot specify exact cause for this hyperglycemia in all cases. However, previous studies have demonstrated that surgical trauma can increase the stress hormone cortisol, along with catecholamines, which can induce insulin resistance, finally resulting in hyperglycemia (Duggan et al 2017;Peacock 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cannot specify exact cause for this hyperglycemia in all cases. However, previous studies have demonstrated that surgical trauma can increase the stress hormone cortisol, along with catecholamines, which can induce insulin resistance, finally resulting in hyperglycemia (Duggan et al 2017;Peacock 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is associated with an activated inflammatory system and leads to organ damage 1 . Perioperative hyperglycemia is common in surgical patients and is associated with poor postoperative clinical outcomes 2–5 . Perioperative hyperglycemia is common in cardiac surgery owing to highly invasive procedures and cardiopulmonary bypass (CPB) 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a prevalent metabolism disorder displayed as hyperglycemia. Long-term hyperglycemia is a risk factor of endocrine disease development because of defi ciency in insulin resistance and/or release (1). Along with advancement of living standards, the incidence and morbidity of diabetes mellitus increases gradually in humans globally, and the number of diabetic patients is estimated to rise to 592 million in 2035 (2).…”
Section: Introductionmentioning
confidence: 99%